Behaviour of peat-added composite bricks in low-cost building construction. (8th December 2014) - Islam, Syed Mofachirul; Hashim, Roslan; Saiful Islam, A. B. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Composite building materials, which can be locally developed with available peat soil, have great potential of application in the construction industry. Utilizing available peat and taking advantage of compressed stabilization technics, peat brick may be environmentally sustainable compared to the conventional building materials. The present study deals with the development of peat bricks, evaluation of its behavior and its application in construction industry. Performance of solid bricks using peat, siliceous sand, and cement in various types of constructional applications have been investigated. The compressive strength and unit weight reduce significantly and water absorption values rise up with increased replacement of peat in aggregation. The effect of 54% volumetric replacement with peat does not exhibit any sudden brittle fracture even when the applied load exceeds the ultimate loads. This peat brick concept can be materialized in building construction in a comparatively affordable cost.